Avaliação do estado nutricional de indivíduos adultos sadios de classe média: ingestão energética e protéica, antropometria, exames bioquímicos do sangue e testes de imunocompetência Assessment of nutritional status of healthy middle class young and adult subjects living in Botucatu, State of S. Paulo, Brazil: energy and protein intakes, anthropometric and blood biochemical estimations and immunocompetence tests - Marco Aurélio de Carvalho Anselmo; Roberto Carlos Burini; Aparecida Yooko Outa Angeleli; Norma Gerusa da Silva Mota; Álvaro Oscar Campana (Universidade de São Paulo, 1992)
Foram estudados parâmetros relacionados ao estado nutricional de 151 adultos sadios, pertencentes à classe média e residindo em Botucatu, SP, Brasil. Valores antropométricos foram maiores nos homens, com exceção da prega tricipital e da área adiposa do braço. O aumento da idade associou-se a aumento dos valores da massa muscular (homens e mulheres) e do peso do corpo, da prega tricipital e da área adiposa do braço (mulheres). Os resultados antropométricos aproximaram-se dos valores referenciais internacionais, mas não foram inteiramente concordantes com eles, sendo inferiores para o peso corpóreo e circunferência e área musculares do braço. Nos indivíduos de menos de 50 anos, os valores da ingestão energética foram ligeiramente inferiores aos níveis recomendados. A ingestão protéica foi adequada. Os valores médios das proteínas e lípides do soro foram similares aos valores de referência. Testes de hipersensibilidade cutânea são apresentados como uma prova funcional para avaliação do estado nutricional. Nutritional status was assessed in 151 middle-class healthy adult individuals (69 medical students, 18-29 y, 34 males, 35 females); 48 university personnel, 30-49 y, 24 males, 24 females; and their older relatives, 34 subjects, 50-79 y, 19 males, 15 females) living in Botucatu, S. Paulo. Methods included anthropometric measurements, energy and protein intakes, blood biochemical analyses and cutaneous delayed hypersensitivity tests. Anthropometric measurements showed higher values in men, with the exception of the triceps skifold thickness (higher in women) and of the arm fat area (higher in the older age female groups); aging seemed to be associated with increases of weight, arm muscle variables and with arm fat accumulation in women and with increases of arm muscle variables in men. The values for anthropometric measurements were in general higher than those found in other Brazilian studies; on the other hand, they approximate to but do not entirely agree with the data representative of the international referential adult population: differences were mainly concerned with body weight and upper arm muscle parameters, which were lower in our sample. As regards energy intake, values found in subjects under 50 years of age were lower than the recommended dietary allowances; averages found for protein intake were above the level recommended by WHO/FAO/UNU (1985). The mean values for serum proteins and lipids were similar to those of referential data. As regards the hypersensitivity tests, it was found that none of the individuals challenged with four antigens (PPD, Candidin, Vaccinia and phytohemagglutinin) presented less than two positive skin reactions. Besides, all the subjects challenged with phytohemagglutinin had positive reaction to this direct lymphocyte stimulator.